PROFESSOR, TRABALHO E SÁUDE: AS POLÍTICAS EDUCACIONAIS, A MATERIALIDADE HISTÓRICA E AS CONSEQÜÊNCIAS PARA A SAÚDE DO TRABALHADOR-PROFESSOR - Sonia R. Landini (Universidade do Oeste Paulista, 2007)
This paper undertakes a reflection concerning the social practice in the school, which has motivated the search for comprehension about the processes of constitution of the school culture, understanding culture as social practice. With the social transformations in the direction of the capital accumulation, the education is characterized by its marketing meaning, having as a goal the individual's formation, reinforcing the capitalist logic of production. In this context, the teacher actuation is characterized by changes in its form, in its objectives and in its destination, supported by the educational policies. In this context, the implications for the health of the teachers configure a problematic picture, resulting, in some cases, in the abandonment of the career and, in other cases, in health problems, related to the extreme suffering. In this scope, we call attention to the relation between social objectivity, the meaning of the work and it's not realization /alienation.